Are The Accountability and Transparency Matters for Zakat Distribution Performance ? : An Empirical Evidence from BAZNAS Province - Nofiansyah, Eka; Pramono, Sigit Eko (International Journal of Zakat, 2024)
This research aims to determine the influence of the Quality of Provincial BAZNAS Financial Reports as measured through Accountability and Transparency on the financial performance of the Allocation to Collection Ratio (ACR). The importance of measuring the ACR ratio is because this is in accordance with the opinion of the majority of ulama and the zakat core principles guidelines that zakat received in one year is also distributed in the same year. This ratio helps measure how much zakat funds were distributed in that year. Calculating this ratio can help improve OPZ's reputation by showing muzakki that the funds have been distributed to mustahik. This research uses descriptive research methods with a quantitative approach. The type of data used in this research is secondary and primary data through questionnaires filled out by 21 Provincial BAZNAS as well as Financial Reports for each Provincial BAZNAS. The results of this research show that the Principles of Accountability and Transparency of Provincial BAZNAS Financial Reports fall into the "Very Good" criteria. Then Accountability and Transparency of financial reporting also have a significant influence on ACR's financial performance.